Sol-Gel Technology for Innovative Fabric Finishing - A Review - Wan Norfazilah, Wan Ismail (SpringerLink, 2016)
Sol–gel technology continues to interest researchers from both industries and governmental institutions in many parts of the world decades after its discovery. It offers efficient and high-purity production of nanopowders, fibres, solid structures and thin-film coatings. Possible applications of sol–gel technology can be found in a wide range of sectors, such as pharmacy, medicine, construction, aerospace, transport, food industry, optics, agriculture, semiconductor devices, catalysis and biotechnology. Also in the textile sector, sol–gel technology is expected to lead the production of fabrics with completely novel properties or the combination of various functions in one fabric. The sol–gel reaction is easy to perform and does not require special conditions and high temperatures. The reaction consists of a series of simple hydrolysis and condensation reactions. This paper presents an overview of sol–gel technology and discusses the fabric functions that can be achieved by the technology.